Race in Sweden Racism and Antiracism in the World's First 'Colourblind' Nation - Hübinette, Tobias (Taylor & Francis, 2023)
Race in Sweden is an introduction to, and a critical investigation of, the Swedish relationship to race in the post-war and contemporary eras. This relationship is fundamentally shaped by an ideology of colourblindness, with any kind of race talk being taboo in public discourse and everyday language use, and in practice forbidden in official and institutional language. A study of a country which was until recently strikingly white but has become extremely diverse, yet where the legacy of Swedish whiteness co-exists with a radical, colourblind, antiracist ideology, Race in Sweden will appeal to scholars across the social sciences and humanities with interests in race and ethnicity, whiteness and Nordic studies.Chapters 2 and 3 of this book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.